Engaging children and youth in Africa : methodological and phenomenological issues - Massart, Guy; Ntarangwi, Mwenda (CODESRIA, Council for the Development of Social Science Research in Africa = Conseil pour le developpement de la recherche en sciences sociales en Afrique, 2015)
Representing research from east, central, west, and southern Africa, Engaging Children and Youth in Africa provides a well-balanced analysis of on-the-ground data with methodological and phenomenological issues that abound in much of research in Africa today. With an introduction that charts out some of the most critical approaches in African-centred research on children and youth, contributors to this volume give the reader a glimpse of the product of engaged research that places children and youth at the centre of analysis. The authors follow recent studies that have insisted on seeing African childhood and youth beyond constraining Western notions of vulnerability or innocence, to capture the ways in which recent advances in technology, the intensification of global processes, and continued weakening of the nation-state have not only contributed to new ways of being children and youth but how they have also provided a new lens through which to study social change.